Exploring the effect of social media information quality, source credibility and reputation on informational fit-to-task: Moderating role of focused immersion. (February 2018) - Zha, Xianjin; Yang, Haijuan; Yan, Yalan; Liu, Kunfeng; Huang, Chengsong
Abstract: Social media have caused information overload for users who normally have limited information processing capability, thus making the issue of task-information fit become critical. The Elaboration Likelihood Model (ELM) provides a theoretical underpinning for understanding the informational influence processes underlying the effectiveness of dual-route persuasion and attitude change. Drawing on the ELM, the current study explores the effectiveness of dual-route persuasion on informational fit-to-task so as to highlight the importance of task-information fit. Specifically, the current study explores the effects of the central route (information quality of social media) and the peripheral route (source credibility of social media and reputation of social media) on informational fit-to-task with focused immersion as an ability variable. The results indicate that focused immersion positively moderates the effect of information quality on informational fit-to-task and negatively moderates the effect of reputation on informational fit-to-task. The findings and their implications are discussed. Highlights: The ELM proposed the informational influence processes of dual-route persuasion. Informational fit-to-task in the context of social media is examined from the ELM. The positive and negative moderating effect of focused immersion is explored. Following the task-technology fit, informational fit-to-task is highlighted.